Emergency rollout and conversion procedures during the three-arm robotic open-thoracotomy-view approach. (29th November 2021) - Sakakura, Noriaki; Nakada, Takeo; Shirai, Suguru; Takahara, Hirotomo; Suzuki, Ayumi; Takahashi, Yusuke; Kuroda, Hiroaki
Abstract: OBJECTIVES: To conduct robotic lung resections (RLRs) with views similar to those in open-thoracotomy surgery (OTS), we adopted a vertical port placement and confronting upside-down monitor setting: the robotic open-thoracotomy-view approach (OTVA). We herein discuss the procedures for emergency rollout and conversion from the robotic OTVA to OTS or video-assisted thoracoscopic surgery (VATS). METHODS: We retrospectively reviewed the cases of 88 patients who underwent RLR with three-arm OTVA using the da Vinci Xi Surgical System between February 2019 and July 2021. Robotic ports were vertically placed along the axillary line, and 2 confronting monitors and 2 assistants were positioned on each side of the patient. Three possible conversions were prepared: (i) emergency thoracotomy using an incision along the ribs in a critical situation, (ii) cool conversion using vertical incision thoracotomy in a calmer condition and (iii) conversion to confronting VATS. All staff involved in the surgery repeatedly rehearsed the emergency rollout in practice. RESULTS: No emergent or cool conversion to OTS occurred. Two patients (2.3%) experienced confronting VATS conversions. One patient underwent an urgent conversion for a moderate haemorrhage from a pulmonary artery branch during left upper lobectomy in the introduction phase. Another patient underwent a calmer conversion during an extended RS6 + S10a segmentectomy, where staples could not be inserted appropriately due to lung lacerations. In all patients, postoperative courses were uneventful. CONCLUSIONS: The OTVA setting is a possible option for RLRs. This report describes the emergent rollout and subsequent conversion procedures for this method. Abstract : We recently reported the 'open-thoracotomy-view approach (OTVA)' using vertical port placement and confronting upside-down (CUD) monitor settings to conduct robotic lung resections (RLRs) with views similar to those in open-thoracotomy surgery (OTS) [1].